Self-Reported Walking Pace and Risk of Cardiovascular Diseases: A Two-Sample Mendelian Randomization Study - Chen, Lu; Sun, Xingang; He, Yuxian; Zheng, Liangrong (Frontiers in Genetics, 2022)
Background: In observational studies, the self-reported walking pace has been associated with the risk of cardiovascular diseases (CVD); however, whether those associations indicate causal links remain unclear. We performed two-sample Mendelian randomization (MR) analyses to evaluate the causal effect of walking pace on several CVD outcomes, including atrial fibrillation (AF), heart failure (HF), any stroke, ischemic stroke (IS), and IS subtypes. Methods: Genetic variants associated with self-reported walking pace were selected as instrumental variables (IVs) from the latest genome-wide association studies (GWAS). Summary-level data for outcomes were obtained from corresponding GWAS and the FinnGen consortium. The random-effects inverse-variance weighted (IVW) method was used as the main MR analysis, supplemented by replication analyses using data from the FinnGen. To explore the effect of pleiotropy due to adiposity-related traits, we further conducted MR analyses by excluding the adiposity-related SNPs and regression-based multivariable MR adjusting for body mass index (BMI). Results: MR results indicated significant inverse associations of self-reported walking pace with risks of AF [odds ratio (OR), 0.577; 95% confidence interval (CI), 0.442, 0.755; P = 5.87×10-5], HF (OR, 0.307; 95% CI, 0.229, 0.413; P = 5.31×10-15), any stroke (OR, 0.540; 95% CI, 0.388, 0.752; P = 2.63×10-4), and IS (OR, 0.604; 95% CI, 0.427, 0.853; P = 0.004), and suggestive inverse association of self-reported walking pace with cardioembolic stroke (CES) (OR, 0.492; 95% CI, 0.259, 0.934; P = 0.030). Similar results were replicated in the FinnGen consortium and persisted in the meta-analysis. However, there was no causality between walking pace and large artery stroke (OR, 0.676; 95% CI, 0.319, 1.434; P = 0.308) or small vessel stroke (OR, 0.603; 95% CI, 0.270, 1.349; P = 0.218). When excluding adiposity-related IVs and adjusting for BMI, the associations for HF and any stroke did not change substantially; whereas, the associations for AF, IS, and CES were weakened. Conclusion: Our findings suggested that genetically predicted increasing walking pace exerted beneficial effects on AF, HF, any stroke, IS, and CES. Adiposity might partially mediate the effect of walking pace on AF, IS, and CES.